Tekwe Method Creativity in Teaching Arabic Language/ طريقة "Tekwe" إبداع في تعليم اللغة العربية - Efendi, Aprijon; Pamil, Jon; Halomoan, Halomoan; Yani, Achmad; Ma’ali, Abul (Ijaz Arabi Journal of Arabic Learning, 2024)
The "Tekwe" method is a unique method of learning Arabic that is applied in Kampung Arab. This study aims to reveal and explain the "Tekwe" method in learning Arabic in the Arabic language course community. The research method used in this research is qualitative research with a case study approach. Data were collected through observation, interviews, and documentation, which were then analyzed using qualitative analysis. Interviews were conducted with the head of the Al-Istiqomah Islamic Boarding School, several teachers, students, and the community. The subjects in the study were the Head of the Islamic Boarding School, teachers, and students. The results of this study are that the Arab Village of Kebumen (KAK) is implemented by students who study in the Arab Village of Kebumen (KAK) and must live in a "mask or homestay" for 14 days following learning activities. The curriculum is designed to use the "Tekwe" Method; creativity in Arabic language learning focuses on communication; teachers are creative in choosing materials and strategies and using media. The head of the Islamic boarding school involves the local community in learning Arabic, carrying out social activities with the community in Arabic, and encouraging the community to speak Arabic with students and teachers.